The influence of spirituality in the workplace on the satisfaction of private sector employees - Albuquerque, Marcio Roberto Branco (2023)
Work plays a fundamental role in human life, as it is not only a means of survival, but also a lever for social, organizational and spiritual experiences, producing meaning, joy and purpose in life. Based on this view, we proposed the following research question: What is the influence of spirituality on the various constructs that form Satisfaction with the workplace in the Brazilian oil and gas industry?” To answer this question, we applied a questionnaire that gathers the scales of Spirituality by Liu and Robert (2011) and Satisfaction with the Workplace by Siqueira (2008). We collected and analyzed using the SEM-PLS 514 complete questionnaires. This technique was applied using SmartPLS 2.0 software. The results indicate that spirituality positively influenced Satisfaction with Wage, Boss, Promotions and Tasks. The only relationship that was not statistically supported was Satisfaction with Coworkers. This result is very interesting as it goes against the literature and points to a peculiarity of great competition between coworkers, which can make the environment quite difficult for management. The theoretical contribution of this study lies in the presentation and testing of the SJS scale in an environment different from its first application, which was in the public sector. The practical contribution is to point out issues that can be worked on by managers, bringing short and long-term gains to satisfaction with the workplace and, consequently, greater employee engagement and commitment.